2014
DOI: 10.1194/jlr.m044032
|View full text |Cite
|
Sign up to set email alerts
|

c9,t11-Conjugated linoleic acid ameliorates steatosis by modulating mitochondrial uncoupling and Nrf2 pathway

Abstract: Oxidative stress, hepatic steatosis, and mitochondrial dysfunction are key pathophysiological features of nonalcoholic fatty liver disease. A conjugated linoleic acid (CLA) mixture of cis9,trans11 (9,11-CLA) and trans10,cis12 (10,12-CLA) isomers enhanced the antioxidant/detoxifying mechanism via the activation of nuclear factor E2-related factor-2 (Nrf2) and improved mitochondrial function, but less is known about the actions of specific isomers. The differential ability of individual CLA isomers to modulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 52 publications
4
33
0
Order By: Relevance
“…Our results suggest that the c9,t11 isomer increased expression of cytochrome c, while t10,c12 isomer increased expression of VDAC. The former observation is consistent with Mollica et al [42] that the c9,t11 isomer, but not the t10,c12 isomer, induced higher cytochrome c activity in Wistar rats. There are currently no reports of CLA's effect on VDAC, however, it was reported that other polyunsaturated fatty acids, DHA and eicosapentaenoic acid (EPA), did not increase VDAC expression in male Wistar rats [43].…”
Section: Discussionsupporting
confidence: 91%
“…Our results suggest that the c9,t11 isomer increased expression of cytochrome c, while t10,c12 isomer increased expression of VDAC. The former observation is consistent with Mollica et al [42] that the c9,t11 isomer, but not the t10,c12 isomer, induced higher cytochrome c activity in Wistar rats. There are currently no reports of CLA's effect on VDAC, however, it was reported that other polyunsaturated fatty acids, DHA and eicosapentaenoic acid (EPA), did not increase VDAC expression in male Wistar rats [43].…”
Section: Discussionsupporting
confidence: 91%
“…The presented data suggest that the beneficial activity of CLA is mediated at least in part by its ability to improve systemic antioxidant and detoxifying defenses via the activation of the Nrf2 pathway. Moreover, on the basis of our previous studies indicating the ability of the cis 9 trans 11 CLA to activate this pathway (17,18), it can be inferred that this isomer may be responsible for the neuroprotective activity of the CLA mixture. Further research is currently in progress to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 88%
“…Such activation of this defensive mechanism by CLA, characterized by a hormetic/ biphasic dose-response pattern (i.e., low-dose stimulation and high-dose inhibition), is not completely unexpected, and it is shared by n-3 PUFAs (DHA and EPA) (16,45). Moreover, the ability of CLA and PUFA to trigger Nrf2 activity (16)(17)(18)46), as well as their pro-oxidant (23,47) and antioxidant effects (45,48), are consistent with the hormetic effects of ROS on Nrf2 pathways (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the liver tissue analysis were not completed from the current study, it has been suggested that increased liver weight by CLA, particularly associated with the trans ‐10, cis ‐12 isomer, may be due to tremendous effects of CLA on fat mobilization from adipose tissue and increased hepatic lipogenesis . Others reported that the effect of CLA on hepatic steatosis was reversible and CLA also reduced high‐fat diet induced hepatic steatosis in rats . Recent meta analysis focusing on CLA and human liver function (as serum markers) reported that CLA supplementation is linked to an increase of one serum marker, aspartate aminotransferase (AST), whereas no links have been found with two other markers, alanine aminotrasnferase (ALT) and alkaline phosphatase (ALP) .…”
Section: Discussionmentioning
confidence: 88%